Pregled jelovih rastišč v Sloveniji - Dakskobler, Igor (Zbornik gozdarstva in lesarstva, 2009)
The article gives an overview of silver fir sites in the territory of Slovenia. We provided a list and a short description of ten silver fir (beech-silver fir, spruce-silver fir) communities. Some of them grow on fresh to moist, neutrophilic or acidophilic sites of the submontane and montane belt (Galio-Abietetum, Bazzanio-Abietetum, Polysticho setiferi-Abietetum), while others prefer very rocky calcareous or silicate sites with initial soil (e.g. Ribeso alpini-Piceetum, Neckero-Abietetum, Calamagrostio-Abietetum, Paraleucobryo-Abietetum). The silver fir has a significant ecological, biotopical and economic role in certain beech (silver fir-beech) communities (e.g. Omphalodo-Fagetum, Homogyno sylvestris-Fagetum, Anemono-Fagetum), but it also grows in most spruce communities, in larch stands (Rhodothamno-Laricetum) and in Alpine dwarf pine stands (Rhododendro hirsuti-Pinetum prostratae= Rhodothamno-Rhododendretum hirusti).
Keywords: Abies alba; bela jelka; fitocenologija; gozdne združbe; jelovi gozdovi; phytosociology; sintaksonomija; Slovenia; Slovenija